SEVERAL DOSAGES OF COW MANURE AND SPACING TOWARDS GROWTH AND GREEN BEAN(Vigna raidata L.) PRODUCTION IN BONE BOLANGO REGENCY - Amiruddin Amir (AGROLAND: The Agricultural Sciences Journal, 2014)
This research aimed to find out the result of green bean production towards the use of cow manure, to find out one spacing that can improve the production of green bean as well as to find out interaction between the use of cow manure  and spacing towards the production of green bean. This research was done at Suka Damai Village of Bolango Utara District in Bone Bolango Regency. This activity was done during the months of January to March 2012. This research used experimental method by using 2 factors in the form of Random Group Pattern. The first treatment was given by using the following manure dosage: P0 : Zero manure, P1 : Cow manure dosage of 5 ton/ha, P2 : Cow manure dosage of 10 ton/ha. Then the second treatment was the spacing in the following: J1 : 40 cm x 15 cm, J2 : 40 cm x 20 cm, J3 : 40 cm x 25 cm. Data were analyzed by using Analysis Of Variance and to find out the influence of dominant treatment by performing Honesty Significant Different Test. The result of the research shows that the treatment of P1J3 or cow dosage manure of 5 ton/ha with the spacing of 45 cm x 25 cm can give good result. Key Words: Green Bean Plant, Cow Manure and Spacing